A germaaluminocene. Issue 11 (21st February 2020) - Albers, Lena; Tholen, Patrik; Schmidtmann, Marc; Müller, Thomas
Abstract : Boron vs. aluminum: the synthesis of a borole complex of Ge(ii ) is reported. Changing just the element from boron to aluminum unexpectedly yields an unprecedented neutral germaaluminocene. Abstract : The reactions of dipotassium germacyclopentadienediide with two Group 13 dichlorides, Cp*BCl2 and Cp*AlCl2, yield two structurally different products. In the case of boron a borole complex of germanium(ii ) is obtained. The aluminium halide gives an unprecedented neutral germaaluminocene. Both compounds were fully characterised by multinuclear NMR spectroscopy supported by DFT computations. The molecular structure of the germaaluminocene was determined by XRD.